2019
DOI: 10.1063/1.5097360
|View full text |Cite
|
Sign up to set email alerts
|

Quantization in magnetoresistance of strained InSb whiskers

Abstract: Strain influence on the longitudinal magnetoresistance for the n-type conductivity InSb whiskers doped by Sn to concentration 6•10 16-6•10 17 сm-3 was studied in the temperature range 4.2-40 K and magnetic field up to 10 T. The Shubnikov-de Haas oscillations at low temperatures were observed in the strained and unstrained samples in all range of doping concentrations and magnetic fields. The character of longitudinal magnetoresistance dependences was analyzed and compared with theoretical one. The whisker magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Comparing these two figures, it is clear that the longitudinal resistance is less than the transverse one that explains prevalence of the surface conductivity in the transverse geometry of the sample due to the whisker coreshell structure. A similar phenomenon was found for InSb samples, where an increase in the doping concentration of the alloying substance was found, approaching the surface of whiskers [16].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Comparing these two figures, it is clear that the longitudinal resistance is less than the transverse one that explains prevalence of the surface conductivity in the transverse geometry of the sample due to the whisker coreshell structure. A similar phenomenon was found for InSb samples, where an increase in the doping concentration of the alloying substance was found, approaching the surface of whiskers [16].…”
Section: Discussionsupporting
confidence: 80%
“…The NMR maximum value achieves 7 % at magnetic field induction 4.5 T and temperature 4.2 K. Similar effect was revealed in [14] for Ge whiskers from the insulating side of the MIT, however, NMR effect was sufficiently weak in comparison to GaPxAs1-x (x=0.4) whiskers. Besides the NMR effect was observed in the InSb [15,16] and GaSb [17] whiskers at high magnetic fields and low temperatures. The analysis of NMR changes with temperature rise has shown that should take into account two characteristic parameters:…”
Section: Formentioning
confidence: 90%
“…Semiconductor whiskers have unique properties due to miniature dimensions leading to arising mesoscopic effects such as low temperature superconductivity [1], negative magnetoresistance [2], arising Berry phase [3] etc.. On the other side, they are prospective for design of microsensors of different physical values [4] including the sensors of humidity. The modern humidity sensors were elaborated using various materials, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Negative magnetoresistance effects were analyzed in undeformed semiconductors based on InSb at low temperatures due to the scattering mechanisms of different charge carriers [7][8][9][10][11]. Besides, negative magnetoresistance phenomena were considered in deformed indium antimonide whiskers of n-type conductivity with different doping concentration in the range 6´10 16 -6´10 17 сm -3 [12].…”
Section: Introductionmentioning
confidence: 99%